Combining SGLT2 Inhibition With a Thiazolidinedione Additively Attenuate the Very Early Phase of Diabetic Nephropathy Progression in Type 2 Diabetes Mellitus - Han, Eugene; Shin, Eugene; Kim, Gyuri; Lee, Ji-Yeon; Lee, Yong-ho; Lee, Byung-Wan; Kang, Eun Seok; Cha, Bong-Soo (Frontiers in Endocrinology, 2018)
Although both sodium glucose co-transporter 2 inhibition by dapagliflozin and thiazolidinedione, pioglitazone have glucose-lowering and anti-inflammatory effects, the therapeutic efficacy of their combination on diabetic nephropathy has not been investigated. 9-week-old male db/db mice were randomly assigned to 4 groups and administrated with (1) vehicle, (2) dapagliflozin, (3) pioglitazone, or (4) dapagliflozin and pioglitazone combination. Human proximal tubule (HK-2) cells were treated with glucose or palmitate acid in the presence of medium, dapagliflozin, pioglitazone, or both. Glomerular tuft area and mesangial expansion of the kidney more reduced in the combination group compared to control and single therapy groups. Podocyte foot process width and glomerular basement membrane thickness decreased regardless of treatment, while the combination group showed the slowest renal hypertrophy progression (P<0.05). The combination treatment decreased MCP-1, type I and IV collagen expression in the renal cortex. Only the combination treatment decreased the expression of angiotensinogen, IL-6, and TGF-β while it enhanced HK-2 cell survival (all P<0.05). In conclusion, dapagliflozin and pioglitazone preserved renal function, and combination therapy showed the greatest benefit. These findings suggest that the combination therapy of dapagliflozin with pioglitazone is more effective than the single therapy for preventing the progression of nephropathy in patients with type 2 diabetes.